Causative Factors Associated with Dry Socket; A Retrospective Study Among the Patients Visiting REU Clinics. - Alabdali, Jarrah; Alsadani, Mohammad; Almutlaq, Mohammed; Thafrah, Saud Bin; Alzabin, Maher; Sheker, Mohammed; Qamar, Zeeshan (International Journal of Health Sciences, 2023)
Purpose: There are various factors associated with the incidence of dry socket, which includes operator experience, perioperative crown, and root fractures, periodontal disease, posterior teeth, and, interestingly, the use of mental health medications to be significant independent risk factors for the development of alveolar osteitis. This study aims to determine the risk factors associated with dry socket and to compare the prevalence of dry socket on the basis of gender, smoking habit, systemic condition, extraction site and use of antibiotics. Methodology: This is a retrospective study using the patients' files at Muneseya campus, Riyadh Elm University. A total of 385 patient files were accessed after seeking approval from the hospital director. Information from patients' files was recorded including gender, operator's level, habits, medical history and extraction site. Results: According to the findings, the percentage of male participants was 70.9%, whereas the percentage of female participants was 29.1%. The findings indicate that 25.3% of the population suffers from systemic illness, whereas the remaining 74.7% does not have any systematic disease. Dry sockets, which are caused by inflammation of the alveolus bone, are present in upper teeth 40% of the time, whereas lower teeth inflammation affects 60% of individuals with lower teeth. Unique Contribution to Theory, Policy and Practice: In this study significant differences were observed for dry socket prevalence when compared the groups on the basis of smoking, systemic disease and gender.